The Sm protein methyltransferase PRMT5 is not required for primordial germ cell specification in mice. (17th December 2014) - Li, Ziwei; Yu, Juehua; Hosohama, Linzi; Nee, Kevin; Gkountela, Sofia; Chaudhari, Sonal; Cass, Ashley A; Xiao, Xinshu; Clark, Amander T
Abstract PRMT5 is a type II protein arginine methyltransferase with roles in stem cell biology, reprograming, cancer and neurogenesis. During embryogenesis in the mouse, it was hypothesized that PRMT5 functions with the master germline determinant BLIMP1 to promote primordial germ cell (PGC) specification. Using a Blimp1‐Cre germline conditional knockout, we discovered that Prmt5 has no major role in murine germline specification, or the first global epigenetic reprograming event involving depletion of cytosine methylation from DNA and histone H3 lysine 9 dimethylation from chromatin. Instead, we discovered that PRMT5 functions at the conclusion of PGC reprograming I to promote proliferation, survival and expression of the gonadal germline program as marked by MVH. We show that PRMT5 regulates gene expression by promoting methylation of the Sm spliceosomal proteins and significantly altering the spliced repertoire of RNAs in mammalian embryonic cells and primordial cells.